A Single‐Crystalline Hierarchical Zeolite via an Oriented Co‐Growth of Nanocrystals Based on Synergy of Polyelectrolytes and Hetero‐Atoms. Issue 10 (30th March 2020) - Shao, Yuanchao; Wang, Yichen; Liu, Xuefei; Li, Tianduo; Haydel, Philip Ryan; Tatsumi, Takashi; Wang, Jingui
Abstract: Hierarchical zeolites have attracted great attention due to the integration of mesopores and/or macropores into the microporous crystalline framework, which decreases the steric and diffusional limitations in the small‐size micropores of zeolites. Among them, single‐crystalline hierarchical zeolites are much desirable due to fewer crystalline defects, higher mechanical stability, and less blocking of the uniform direction of microporous channels, which show high catalytic performance in conventional industrially‐important small‐molecule reactions, and heavy‐oil catalytic cracking, biomass catalytic conversion, polymer degradation, etc. Here, a novel one‐pot kinetics‐dominated strategy was developed to synthesize titanium‐containing single‐crystalline hierarchical zeolites via synergy of polyelectrolytes and framework hetero‐atoms by means of concentrating the starting precursor, restriction of the Oswald ripening to protect nano‐crystals, as well as oriented attachment between nano‐crystals. The resultant zeolite displayed a much higher catalytic performance in olefin epoxidation and cyclohexanone ammoximation than those of conventional pure‐microporous zeolites. Abstract : Nanocrystal comprised nanocrystals : Single‐crystalline nano‐zeolites formed via an orientating arrangement of 20–50 nm nanocrystals